1996
DOI: 10.1007/bf02306284
|View full text |Cite
|
Sign up to set email alerts
|

Patient satisfaction with decision-making for breast cancer therapy

Abstract: When informed of the diagnosis and treatment options in an unhurried, supportive setting, and when encouraged to seek further consultations as desired, breast cancer patients make appropriate therapeutic choices about mastectomy or breast conservation therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Some research suggests that information seeking among breast cancer patients was associated with better physical functioning or physical quality of life six months post-treatment [37]. Additionally, research has found that patients who are better informed report better emotional well-being [38], better satisfaction with medical treatment [39], and improved physical functioning [40]. Patient information seeking behavior, sources of information, and informational needs change over time.…”
Section: Resultsmentioning
confidence: 99%
“…Some research suggests that information seeking among breast cancer patients was associated with better physical functioning or physical quality of life six months post-treatment [37]. Additionally, research has found that patients who are better informed report better emotional well-being [38], better satisfaction with medical treatment [39], and improved physical functioning [40]. Patient information seeking behavior, sources of information, and informational needs change over time.…”
Section: Resultsmentioning
confidence: 99%
“…Many patients who undertake a passive role in decision-making still want to be well informed. Increases in knowledge, satisfaction, treatment compliance, and quality of life have been reported as positive outcomes of adequate information provision [18][19][20]. Not having enough information has been linked to dissatisfaction with care and reduced wellbeing [17,21].…”
Section: Introductionmentioning
confidence: 98%
“…Many of these will be younger women who prefer greater involvement in treatment decision-making and their needs for information may differ from older women (Degner et al ., 1997). In general, patients who are better informed experience greater emotional, social and physical well-being (Fallowfield et al ., 1994), better clinical outcomes, quality of life (Fallowfield et al ., 1994) and satisfaction with care (Weiss et al ., 1996). Timing of information is important.…”
Section: Discussionmentioning
confidence: 99%